Relationship of depth of invasion of tumour with neck node metastasis in oral squamous cell carcinoma: a clinico pathological correlation - Roy, Arjun; Sarma, Mridul Kumar; Deka, Muktanjalee; Missong, Ajit Kumar; Choudhury, Mrinmoy Mayur; Choudhury, Yousuf F. (International Journal of Research in Medical Sciences, 2022)
Background: Squamous cell carcinomas of the oral cavity are relatively common among the head and neck cancers. The increasing depth of invasion (DOI) and the microvascular proliferation caused by neoplastic growth might determine proximity to blood vessels and lymphatics, thus facilitating the tumor’s ability to metastasize. The role of tumour DOI as a prognostic parameter for the development of nodal metastases and for the survival of patients with OSCC are important. Aim of the study was to determine the relationship of the DOI of tumor with the neck node metastasis in squamous cell carcinoma of the oral cavity. Methods: This study is conducted in the State cancer institute, Gauhati medical college over a period of 1 year from June 2021 to June 2022 among 100 patients. All patients underwent tumor resection with neck dissection, and the DOI is measured. Results: Out of 100 patients included in the study 66 were males and 34 were females. Maximum number of cases 30% were seen in the age group of 51-60 years. Gingivobuccal sulcus (32%) is the most commonly involved site. Maximum number of nodal meta-stasis present in tumours with DOI>11 mm and minimum nodal metastasis present in tumours with DOI<3 mm. Conclusions: We conclude that tumor DOI is significantly related with neck nodal metastasis in oral cavity squamous cell carcinoma.